Innate and Adaptive Anti-SIV Responses in Macaque Semen: Implications for Infectivity and Risk of Transmission - Suphaphiphat, Karunasinee; Bernard-Stoecklin, Sibylle; Gommet, Céline; Delache, Benoit; Dereuddre-Bosquet, Nathalie; Kent, Stephen J.; Wines, Bruce D.; Hogarth, P. Mark; Le Grand, Roger; Cavarelli, Mariangela (Frontiers in Immunology, 2020)
HIV-1 infection is transmitted primarily by sexual exposure, with semen being the principal contaminated fluid. However, HIV-specific immune response in semen has been understudied. We investigated specific parameters of the innate, cellular and humoral immune response that may affect semen infectivity in macaques infected with SIVmac251. Serial semen levels of cytokines and chemokines, SIV-specific antibodies, neutralization and FcγR-mediated functions and SIV-specific T-cell responses were assessed and compared to systemic responses across 53 cynomolgus macaques. SIV infection induced an overall inflammatory state in the semen. Several pro-inflammatory molecules correlated with SIV virus levels. Effector CD8+ T cells were expanded in semen upon infection. SIV-specific CD8+ T-cells that expressed multiple effector molecules (IFN-γ+MIP-1β+TNF+/-) were induced in the semen of a subset of SIV-infected macaques, but this did not correlate with local viral control. SIV-specific IgG, commonly capable of engaging the FcγRIIIa receptor, was detected in most semen samples although this positively correlated with seminal viral load. Several inflammatory immune responses in semen develop in the context of higher levels of SIV seminal plasma viremia. These inflammatory immune responses could play a role in viral transmission and should be considered in the development of preventive and prophylactic vaccines.